2019
DOI: 10.1159/000498837
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Sensors of Viral RNA Are Involved in the Production of Interleukin-6 via Toll-Like Receptor 3 Signaling in Human Glomerular Endothelial Cells

Abstract: Background/Aims: Dysregulation of interleukin-6 (IL-6) production in residual renal cells may play a pivotal role in the development of glomerulonephritis (GN). Given that Toll-like receptor 3 (TLR3) signaling has been implicated in the pathogenesis of some forms of GN, we examined activated TLR3-mediated IL-6 signaling in cultured normal human glomerular endothelial cells (GECs). Methods: We treated GECs with polyinosinic-polycytidylic acid (poly IC), an authentic double-stranded RNA, and analyzed the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…It has been recently shown that RLRs drive inflammatory macrophage polarization and suppress wound healing macrophages against West Nile virus infection 165 . MDA5 and RIG‐I are involved in the TLR3‐mediated IL‐6 signaling in human glomerular endothelial cells 166 . More interestingly, in vivo delivery of therapeutically active RIG‐I mimetics leads to RIG‐I activation in breast cancer, triggering apoptosis and pyroptosis for immunogenic killing of tumor cells 167 .…”
Section: Rig‐i‐like Receptorsmentioning
confidence: 99%
“…It has been recently shown that RLRs drive inflammatory macrophage polarization and suppress wound healing macrophages against West Nile virus infection 165 . MDA5 and RIG‐I are involved in the TLR3‐mediated IL‐6 signaling in human glomerular endothelial cells 166 . More interestingly, in vivo delivery of therapeutically active RIG‐I mimetics leads to RIG‐I activation in breast cancer, triggering apoptosis and pyroptosis for immunogenic killing of tumor cells 167 .…”
Section: Rig‐i‐like Receptorsmentioning
confidence: 99%
“…ELISA kits for IFN-α and IFN-β were purchased from PBL Assay Science (Piscataway, NJ, USA). siRNA against IFN-β is previously described [7][8][9][10][11][12]. Primer sequences are listed in Table 1.…”
Section: Reagentsmentioning
confidence: 99%
“…Since the expression of TLR3 in resident glomerular cells is confirmed in biopsy specimens from patients with CKD [4,5], regional antiviral host defenses via the activation of TLR3 signaling in the intrinsic glomerular cells have been postulated to be involved in the pathogenesis of some CKD types [4][5][6]. To date, considering the implications of TLR3 signaling in the pathogenesis of CKD, we treated cultured human mesangial cells (MCs) and glomerular endothelial cells (GECs) with polyinosinic-polycytidylic acid (poly IC), an authentic viral doublestranded RNA, and thereafter examined the expressions of representative proinflammatory chemokines and cytokines [6][7][8][9][10][11][12]. Notably, podocytes themselves also reportedly express TLR3 and its downstream signaling pathways, and these axes are presumed to be involved in the pathogenesis of certain CKD forms [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is produced by activated leukocytes and endothelial cells and acts on multiple cells and tissues. 9,10 Furthermore, IL-6 is also involved in the pathogenesis of the cytokine release syndrome (CRS), which is an acute systemic inflammatory syndrome characterized by fever and multiple organ dysfunction.…”
Section: Introductionmentioning
confidence: 99%